Psychometric Evaluation of Dietary Habits Questionnaire for Type 2 Diabetes Mellitus - Sami, Waqas; Ansari, Tahir; Butt, Nadeem Shafique; M. R., Abdul Hamid (IOP Publishing, 2017)
This research evaluated the psychometric properties of English version of dietary habits questionnaires developed for type 2 diabetic patients. There is scarcity of literature about availability of standardized questionnaires for assessing dietary habits of type 2 diabetics in Saudi Arabia. As dietary habits vary from country to country, therefore, this was an attempt to develop questionnaires that can serve as a baseline. Through intensive literature review, four questionnaires were developed / modified and subsequently tested for psychometric properties. Prior to pilot study, a pre-test was conducted to evaluate the face validity and content validity. The pilot study was conducted from 23 October – 22 November, 2016 to evaluate the questionnaires’ reliability and validity. Systematic random sampling technique was used to collect the data from 132 patients by direct investigation method. Questionnaires assessing diabetes mellitus knowledge (0.891), dietary knowledge (0.869), dietary attitude (0.841) and dietary practices (0.874) had good internal consistency reliability. Factor analysis conducted on dietary attitude questionnaire showed a valid 5 factor solution. Directions of loadings were positive and free from factorial complexity. Relying on the data obtained from type 2 diabetics, these questionnaires can be considered as reliable and valid for the assessment of dietary habits in Saudi Arabia and neighbouring Gulf countries population.